2017
DOI: 10.1139/cjpp-2016-0609
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of necroptosis in hearts subjected to various forms of ischemic insults

Abstract: Long-lasting ischemia can result in cell loss; however, repeated episodes of brief ischemia increase the resistance of the heart against deleterious effects of subsequent prolonged ischemic insult and promote cell survival. Traditionally, it is believed that the supply of blood to the ischemic heart is associated with release of cytokines, activation of inflammatory response, and induction of necrotic cell death. In the past few years, this paradigm of passive necrosis as an uncontrolled cell death has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Our data showed increased cell death in hearts from BPA treated mice, especially in the areas containing blood vessels, in the absence of increased apoptotic markers. Necroptosis is a newly discovered pathway of programmed cell death with an essential role in human ischemic injury 72 . RIP 3 is a critical determinant in the necroptotic pathway and is expressed in the myocardium 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed increased cell death in hearts from BPA treated mice, especially in the areas containing blood vessels, in the absence of increased apoptotic markers. Necroptosis is a newly discovered pathway of programmed cell death with an essential role in human ischemic injury 72 . RIP 3 is a critical determinant in the necroptotic pathway and is expressed in the myocardium 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of receptor interacting protein 1 (RIP1) by a drug class referred to as the necrostatins has been shown to retard necroptosis, a form of programmed necrotic-like cell death which has been suggested to underlie pathophysiology of various diseases, including neurodegenerative diseases [ 1 ], acute inflammatory conditions [ 2 ], malignancies [ 3 ] and cardiovascular diseases associated with ischemia (reviewed by [ 4 , 5 ]). Necrostatin-1 (Nec-1, 5-(indol-3-ylmethyl)(2-thio-3-methyl)hydantoin), the first discovered necrostatin [ 6 ], which acts as an allosteric inhibitor of kinase domain of RIP1, has been widely used in some of these studies [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that necrosis in the myocardium and cardiac MDA levels were significantly decreased after postconditioning as compared to the control group. Prolonged ischemia can cause cell loss, however, recurrent short ischemia episodes in short terms in the distal skeletal muscle may have revealed an increase in the resistance to the detrimental effects of the long-term ischemic condition in the heart (17), and thus improved the survival of the cells in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…The process of necrosis was found to be dependent on the activation of the receptor-interacting protein (RIP)1, RIP3, and a mixed-lineage kinase domain-like protein axis. This pathway is activated by TNF-α, which is also present in the cardioprotective signaling pathway of ischemic pre-conditioning (17). The association between TNF inhibitors and myocarfial infarction has been investigated previously and it has been demonstrated that TNF inhibitors offer a reduced MI risk, while some other studies found the risk to be similar when they were compared to DMARDs (6).…”
Section: Discussionmentioning
confidence: 99%